Analisis Produktivitas dan Pendapatan Usahatani Bawang Merah di Kecamatan Wedarijaksa Kabupaten Pati - Putri Damayanti, Evarista; Setiadi, Agus; Handayani, Migie (Universitas Medan Area, 2025)
Shallots are a horticultural crop of high economic value and worth developing. High demand from domestic consumers provides a stable and sustainable market opportunity for shallot farmers. The problem is that shallot production in Wedarijaksa District has decreased, resulting in decreased productivity. This research aims to analyze the value of productivity, analyze the amount of income and the factors that influence the productivity and income of shallot farming in Wedarijaksa District, Pati Regency. The research method used was a survey method with sample determination using proportionate stratified random sampling and the number of samples used was 120 shallot farmers. The data analysis method uses analysis of farming productivity levels, income analysis, and statistical analysis, namely path analysis. The research results show that the average productivity of shallot farming in Wedarijaksa District is 8.35 tons/ha and the average income of shallot farming in Wedarijaksa District is IDR 40,703,163. Based on path analysis, the results showed that the factors that influence shallot productivity include the amount of production, seeds, fertilizer, pesticides and factors that influence shallot farming income include seeds, fertilizer and selling price.